Association between sociodemographic characteristics and anxiety levels of violence-exposed patients admitted to emergency clinic - Hocagil, Hilal; Izci, Filiz; Hocagil, Abdullah Cuneyt; Findikli, Ebru; Korkmaz, Sevda; Koc, Merve Iris (Dove Medical Press Ltd, 2016)
Background: Here we aimed to investigate sociodemographic characteristics, psychiatric history, and association between sociodemographic characteristics and anxiety levels of violence-exposed patients admitted to emergency clinic. Methods: This study consists of 73 violence-exposed patients admitted to emergency clinic who were literate and agreed to participate in the study. A sociodemographic data form created by us to investigate alcohol-substance abuse, suicide attempt, previous history of trauma, self and family history of psychiatric disorders and Beck Anxiety Inventory was given to the patients. Results: Of the patients exposed to violence 63% (n=46) were female and 27% (n=27) were male. Of these patients, 68.5% (n=50) were married, 43.8% (n=25) were workers, 34.2% were housewives, 11% were unemployed, and 11% were civil servants. Of the violence-exposed patients, 56.2% (n=41) were primary school, 21.9% (n=16) were high school, and 21.9% (n=16) were university graduates. Smoking and alcohol use rates were 54.8% (n=40) and 17.8% (n=13), respectively. The most common trauma type was assault using physical force with a ratio of 78.1% (n=57). In addition, anxiety scores were high in 42.5% (n=31) and moderate in 9.6% (n=7) of the patients. Mentioned psychiatric disorder was present in 17.8% (n=13) of the patients and 19.2% (n=14) of the patients' relatives. The correlation between sociodemographic characteristics and anxiety scores revealed that married patients had higher anxiety scores (P < 0.01) and patients assaulted by their parents had lower anxiety scores (P < 0.00). Conclusion: A total of 63% of the violence-exposed patients admitted to emergency room were females, 56.2% were primary school graduates, and 43.8% were factory workers; this result shows that low socioeconomical status and education level affect exposure to trauma especially in females. In addition, similar to 20% of the patients and patients' relatives had a psychiatric disorder and 53.4% of perpetrators were parents, spouses, and children; this result shows that psychiatric history and family relations are one of the issues that should be taken into account and treated.
Keywords: violence; emergency; anxiety